2007
DOI: 10.1038/ng2047
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific transcriptional regulation has diverged significantly between human and mouse

Abstract: We demonstrate that the binding sites for highly conserved transcription factors vary extensively between human and mouse. We mapped the binding of four tissue-specific transcription factors (FOXA2, HNF1A, HNF4A, HNF6) to 4,000 orthologous gene pairs in hepatocytes purified from human and mouse livers. Despite the conserved function of these factors, from 41% to 89% of their binding events appear to be species-specific. When the same protein binds the promoters of orthologous genes, approximately two-thirds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

60
446
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(510 citation statements)
references
References 15 publications
(16 reference statements)
60
446
2
2
Order By: Relevance
“…However, it should be noted that we restricted our analysis to positionally conserved sites, and that these sites found in the mouse genome may actually be conserved in sequence but shifted location within the human genome. Indeed, occupancy of some regulatory factors has been shown to shift in location between mouse and human genomes (12). Moreover, GBSs that are not conserved between mouse and human may be conserved in genomes of other species, and extending our study beyond the current pairwise analysis may be informative.…”
Section: Discussionmentioning
confidence: 90%
“…However, it should be noted that we restricted our analysis to positionally conserved sites, and that these sites found in the mouse genome may actually be conserved in sequence but shifted location within the human genome. Indeed, occupancy of some regulatory factors has been shown to shift in location between mouse and human genomes (12). Moreover, GBSs that are not conserved between mouse and human may be conserved in genomes of other species, and extending our study beyond the current pairwise analysis may be informative.…”
Section: Discussionmentioning
confidence: 90%
“…We found that comparative genomics resulted in many functionally meaningful sites for transcription factors Mef2, Twist and Snail outside ChIPbound regions, probably representing targets from diverse conditions not surveyed experimentally. Similarly, ChIP resulted in many additional sites outside those recovered by comparative genomics: some of these may have been replaced by functionally equivalent non-orthologous sequence, rendering them apparently non-conserved in sequence alignments [122][123][124] ; others may have species-or lineagespecific roles, thus lacking sufficient signal for their comparative detection; finally, some bound sites may be biochemically active yet selectively neutral 125 . It is worth noting, however, that ChIP-bound motifs that were not conserved showed decreased enrichment in muscle/ mesoderm development where the factors are known to act, suggesting that potential lineage-specific roles may lie outside the regulators' conserved functions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for one of their transcription factors, CEPBA, only 0.3% of binding sites were conserved across all five species (Schmidt et al 2010). Transcription factor binding site (TFBS) ''turnover'' and sequence mutation of binding sites are two mechanisms that may explain this high degree of species-specific binding (Odom et al 2007;Schmidt et al 2010). These results raise an important question: How sensitive are alignment-based conservation approaches in predicting regulatory elements?…”
mentioning
confidence: 99%